Intake of Vitamins and Minerals From Voluntarily Fortified Foods and/or Dietary Supplements in School Adolescents in Central-Eastern Poland - Sicińska, Ewa; Pietruszka, Barbara; Januszko, Olga; Jakubowski, Sebastian; Kielak-Biskupska, Kamila; Rolf, Katarzyna; Kaluza, Joanna (Frontiers in Public Health, 2020)
Background: The key issue is whether voluntarily fortified foods and vitamin/mineral supplements available on the market serve public health needs. The study aim was to estimate nutrient intakes from voluntarily fortified foods and vitamin/mineral supplements in relation to the Dietary Reference Intake (DRI) in adolescents (n = 759) aged 13–19 who attended public secondary schools in Central-Eastern Poland. Methods: Data on the consumption of voluntarily fortified foods were collected using a semi-quantitative food frequency questionnaire containing 58 food items. Data on the use of dietary supplements were assessed via an open-ended question. The content of nutrients was estimated using the producer's labeling declaration. The distribution of nutrient intakes according to the percentage of DRI categories (<20%, 20–39.9%, 40–59.9%, 60–79.9%, 80–99.9%, 100–119%, or >120%) was estimated. Results: Consumption of voluntarily fortified foods was a common behavior in adolescents (86.7% of participants), while vitamin/mineral supplements were used by less than one-fifth of them (17.7%). The amounts of nutrient intakes from fortified foods and/or supplements were at different levels: (I) vitamins A, D, calcium, magnesium (>50% of adolescents did not exceed 20% of DRI); (II) vitamins E, B12, iron (>50% of respondents consumed at least 20% of DRI); (III) niacin and pantothenic acid (>50% of respondents consumed at least 40% of DRI); IV) vitamins C, B1, B2, B6, folate, biotin (>50% of participants consumed at least 60% of DRI). In a subgroup of respondents who used fortified foods and supplements simultaneously (n = 126), some nutrients (i.e., vitamins C, B1, B2, B6, niacin, and biotin) were consumed in amounts ≥150% of DRI. Intake above the Tolerable Upper Intake Levels was observed for niacin, vitamin A, B6 and folic acid in individual cases (up to 1.1% of respondents); a higher risk of overconsumption was associated with using vitamin/mineral supplements than voluntarily fortified foods. Conclusion: Adolescents should be educated on how to reasonably use fortified foods and dietary supplements to help to overcome the potential deficiency of nutrients without causing excessive consumption.